2019
DOI: 10.1039/c9ra04218k
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of mild steel corrosion in 0.5 M H2SO4 solution by radish leaf extract

Abstract: The inhibitory effect of radish leaf extract (RLE) on mild steel corrosion in 0.5 M H2SO4 was studied by the weight loss method and the electrochemical method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…Tephrosia purpurea [16] extract prevented the corrosion on the mild steel surface in 1N HCl. Anticorrosive properties of Aegle marmelos [17], Radish leaf [18], Armoracia rusticana [19], and Artemisia herba-alba oil [20] were studied in 0.5 M H 2 SO 4 . Citrus sinensis (orange) [21] and Hardwickia binata roxb [22] were investigated as an environmentally friendly corrosion inhibitor in both HCl and H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Tephrosia purpurea [16] extract prevented the corrosion on the mild steel surface in 1N HCl. Anticorrosive properties of Aegle marmelos [17], Radish leaf [18], Armoracia rusticana [19], and Artemisia herba-alba oil [20] were studied in 0.5 M H 2 SO 4 . Citrus sinensis (orange) [21] and Hardwickia binata roxb [22] were investigated as an environmentally friendly corrosion inhibitor in both HCl and H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The results (Table 3.3) show that there was a continuous decrease in Corrosion rate and continuous increase in the Inhibitor efficiency as the Inhibitor concentration increases. This shows that even though at a pH of 3.15 when the reduction of Hydrogen ion is supposed to be the rate controlling mechanism of the reaction, thus, causing an increase in the corrosion rate, the increase in Temperature to 60 o C, enables a faster precipitation of the corrosion protective film which further ensures that more protective films are being formed that spread across the coupon giving room for only localised corrosion to occur (Li et al, 2019;Rivera-Grau et al, 2012). This observation was supported by (Gunavathy and Murugavel, 2012) which suggested that more corrosion protective film is being precipitated in a solution with Inhibitor as temperature is being increased from 20 o C. A comparison of this observation with the Control solution without Inhibitor (0mg/L Inhibitor concentration) from figure 4.9 shows that the solution without an Inhibitor has the highest corrosion rate and this is because as the hydrogen ion concentration is dominant in the medium, there was no protection for the Coupon giving room for the corrosion product to attack the entire surface of the Coupon which further leads to a general corrosion taking place (Tasić et al, 2018) .…”
Section: Weight Loss Measurementmentioning
confidence: 99%
“…With a rise in Temperature, the Corrosion rate shows increase and decrease with respect to the solubility limit of Iron Carbonate Layer (Farhadian et al, 2020). At the non-film forming conditions (Low pH), increasing the Temperature results to an increase in the Corrosion rate and a decrease in the efficiency (Li et al, 2019). An observation of the results (Figure 3.2) show that the Efficiency of the Inhibitor increases with increase in Inhibitor Concentration for the same pH level.…”
Section: Weight Loss Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Many literatures used 0.5 M H 2 SO 4 during acid cleaning stage of steel and other related alloys. [16][17][18][19][20] The most successful method of minimizing carbon steel degradation is through the development of corrosion inhibitors that shield metals from strong corrosion attack in acidic conditions. At the moment, creative effective, locally sourced, commercially viable, and ecologically acceptable inhibitors are critical for resolving problem of corrosion occurred in the metallic industry.…”
Section: Introductionmentioning
confidence: 99%